Rotator Cuff Tears and Mid-Term Shoulder Outcomes after Intramedullary Nail Fixation for Humeral Shaft Fracture: A Minimum Five-year Follow-up Study - Furuhata R; Tanji A; Nakamura S; Urabe T (Malaysian Orthopaedic Journal)
Introduction: Antegrade intramedullary nail fixation for humeral shaft fractures yields satisfactory union rates. However, one of the related concerns is damage to the rotator cuff during nail insertion, which may affect long-term outcomes. The effect of a rotator cuff lesion on mid- and long-term shoulder outcomes remains unknown. This study aimed to investigate the incidence of rotator cuff tears 5 years or more after intramedullary nailing for humeral shaft fractures and to determine the impact of post-operative rotator cuff tears on mid-term outcomes.